A novel mutation in the DGUOK gene in a Turkish newborn with mitochondrial depletion syndrome - Kiliç, Mustafa; Topaloğlu, Haluk; Yiğit, Sule; Akçören, Zuhal; Seneca, Sara; De Meirleir, Linda; Tokatli, Ayşegül; Dursun, Ali; Sivri, Hatice Serap; Coşkun, Turgay (The Turkish Journal of Pediatrics, 2011)
Deoxyguanosine kinase (DGUOK) catalyzes the first step of the mitochondrial deoxypurine salvage pathway, the phosphorylation of purine deoxyribonucleosides. Mutations in the DGUOK gene have been linked to inherited mitochondrial (mt)DNA depletion syndromes, neonatal liver failure, nystagmus, and hypotonia. We now report a novel homozygous c.34C > T (p.Arg12X) mutation found in an affected newborn of asymptomatic consanguineous parents. Respiratory distress started in the first hours after birth. The patient died at the age of 42 days due to liver failure. This genotype, which is to be expected for a homozygous stop codon mutation in exon 1, is associated with a severe clinical presentation.